(3cJGH GdJhGHjfs - (3YHO Gddg Hf CMeO Hf eMeO Hf bOGeI GdLeGYjdj GdebOSj Ke GdOeTbj GdMfHdj, ehab GdOjf GHf bOGeI , J (B620 (3gs ((3YHO Gddg Hf TajY Hf YeQGf Hf eGdc GdJejei GdMfHdj s)
(3ChdgG (B:s
(3hHYO , agPG cJGH PcQJ ajg HYV CNHGQ GdJhGHjf JThjbkG Edi CNHGQge hJQZjHkG ai CMhGdge s
(3BNQgG (B:s
(3hbGd (B: (3GTgO Cf dG Edg EdG Gddg hCf eMeOkG QShd Gddg BNQ GdcJGH hGdMeO ddg hMOg , hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg GdWjHjf GdWGgQjf CLeYjf s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B67 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B30 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B459s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B398 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B689 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B332 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs